1997
DOI: 10.1038/bjc.1997.305
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclin D1 correlates with early recurrence in superficial bladder cancers

Abstract: Summary Cyclin Dl is a cell cycle regulator essential for G1 phase progression and is frequently overexpressed in several human tumour types as a consequence of gene amplification or chromosomal rearrangements. We analysed the expression of cyclin Dl in 75 patients with transitional cell carcinoma (TCC) to investigate the possible relationship between its expression and clinical outcome as well as histopathological findings using the immunohistochemical method. We observed strong staining (++, > 50% positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
48
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 22 publications
8
48
0
3
Order By: Relevance
“…It was previously reported that overexpression of cyclin D1 correlates with early recurrence in superficial bladder cancers. 11 The results of that study, however, are hampered by the heterogeneous treatment of patients. Moreover, the presence of 50% positive cells was used as the cutoff to define cyclin D1 overexpressing tumors.…”
Section: Predictive Power Of Combined Cyclin D1 P27 Kip1 and Ki67 Indexmentioning
confidence: 98%
See 1 more Smart Citation
“…It was previously reported that overexpression of cyclin D1 correlates with early recurrence in superficial bladder cancers. 11 The results of that study, however, are hampered by the heterogeneous treatment of patients. Moreover, the presence of 50% positive cells was used as the cutoff to define cyclin D1 overexpressing tumors.…”
Section: Predictive Power Of Combined Cyclin D1 P27 Kip1 and Ki67 Indexmentioning
confidence: 98%
“…6 It has been shown to correlate with low-grade, low-stage and papillary tumor growth in primary bladder carcinomas, 9,10 and it has been suggested to play an important role in bladder cancer progression. 11 However, the prognostic significance of cyclin D1 expression in urinary bladder cancer has not yet been determined. 12 Evaluation of Ki67, a proliferation-related antigen, using the MIB-1 antibody has been reported to have a prognostic significance in bladder cancer.…”
mentioning
confidence: 99%
“…Immunohistochemical staining was performed by the method previously described (Shin et al, 1997). Briefly, representative tissue sections from 69 cases were deparaffinized and rehydrated.…”
Section: Immunohistochemical Studymentioning
confidence: 99%
“…Some of the human primary cancers have been found to have amplification or overexpression of the relevant gene locus of cyclin D1 including breast (Gillett et al, 1994;McIntosh et al, 1995;Simpson et al, 1997), oesophagus (Jiang et al, 1992;Adelaide et al, 1995), liver (Zhang et al, 1993;Nishida et al, 1994), head and neck (Callender et al, 1994, Michalides et al, 1995 and urinary bladder cancers (Proctor et al, 1991;Shin et al, 1997).…”
mentioning
confidence: 99%
“…22 Further expression of cyclin D1 in tumours detected by immunohistochemical staining has been associated with patient prognosis in a number of cancers including, breast, squamous cell carcinoma of the head and neck (SCCHN), lung, pancreatic and bladder cancer. [23][24][25][26][27] Until recently, less consideration has been given to the function of the protein product from CCND1 trb . Sawa et al 28 have demonstrated that when overexpressed in human malignant glioma cells, the alternatively spliced forms of cyclin D1 modulate entry into the cell cycle in an inverse manner.…”
mentioning
confidence: 99%